Development of Local Potential-Based Ecosystem Modules in Grobogan Regency to Improve Students' Critical Thinking Ability - Nurul Setiyanika; Sri Sri Ngabekti; Parmin Parmin (Universitas Negeri Semarang, 2023)
The local potential of Grobogan Regency is very diverse, which has the potential as a learning resource that can be integrated into learning biology on ecosystem material to improve students' critical thinking skills needed in the 21st century. Critical thinking enables students to apply decision-making abilities and solve problems in everyday life. day. This study aims to produce a module based on local potential in the Grobogan Regency that is feasible based on the validity, readability, and practicality of the module, and effectiveness to improve critical thinking skills. To develop critical thinking skills these students must obtain teaching materials that facilitate these skills. This research is a research and development (R&D) and one-group pretest-posttest research design. The research instruments were expert validation questionnaires by expert validators and teachers, and module readability and practicality questionnaires by teachers and students, effectiveness was measured from the results of the pretest and posttest conducted on students before and after using the module. Data were analyzed by descriptive quantitative. Based on the results of the validation test for ecosystem modules based on local potential, a score percentage of 85.58% was obtained, including the very valid category. The results of readability and practicality using local potential-based ecosystem modules obtained a score of 80.75% including the good category and 80.41% including the practical category. The N-gain results show an average of 0.62 in the medium category. Based on the results of the development of ecosystem modules based on local potential, Grobogan Regency was declared feasible based on validity, readability and practicality, and effectiveness as teaching materials.